Drug Induced Primary Tubulointerstitial Nephritis: A Retrospective Renal Biopsy Study in A Tertiary Care Hospital - Amey, Rojekar; Chitra, Madiwale (Annals of Pathology and Laboratory Medicine, 2019)
Background: Primary Tubulointerstitial Nephritis (TIN) is inflammation of predominantly tubular & interstitial compartment without involving glomeruli and vessels, which may be due to varied etiologies. Drugs are the most common culprit for Primary TIN worldwide. Here we studied a series of primary TIN in renal biopsies at a tertiary care center. Methods: In this retrospective study of ten year duration, we have studied all cases of primary TIN with history of drug intake. We reviewed these cases for symptoms, etiology and histomorphological features. Results: A total of 54 cases of primary TIN were described. The age range of the patients was 6 to 72 years with mean of 47.8 years. Pedal edema, puffiness of face were the most common symptoms followed by oliguria. Non-Steroidal Anti-Inflammatory (NSAIDs) were found to be the most common group of drugs causing acute TIN resulting in acute kidney injury (AKI). These are followed by antibiotics and ayurvedic/indigenous preparations. Acute TIN was more commonly seen histopathology than chronic TIN. Conclusion: NSAIDs are most common cause of TIN followed by ayurvedic drugs. Timely diagnosis and withdrawal of offending agent with prompt treatment may help to preserve or improve renal function.